(untitled) (Bangladesh Journal of Pharmacology, 2015)
The aim of this study was to synthesize novel amide derivatives of bergapten and evaluate their lipid-lowering and triglyceride-lowering activities in mice. Amide derivatives of bergapten were synthesized by using lactone ring opening strategy in DMSO using NaOH as base followed by alkylation in presence of methyl iodide. The compounds were subjected to preliminary in vivo screening. Fenofibrate (30 mg/kg/day) was used as positive controls in this assay. The lipid lowering activity was evaluated using in vivo Triton model and Triton WR-1339 was used as positive control. Most of the synthesized analogs displayed remarkable plasma triglyceride-lowering activity. Compound 5 showed the best activity with (41%) triglyceride lowering activity. This compound also exhibited the most potent lipid lowering activity displaying 33%, 32% and 29% lowering in total cholesterol, phospholipids, and triglycerides, respectively. The other derivatives showed almost comparable activity with that of the parent molecule.